2017
DOI: 10.1093/alcalc/agx003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Zonisamide on the Development and Course of Alcohol Dependence in Rabbits. A pharmaco-EEG study

Abstract: A pharmaco-EEG method was used to determine the influence of a new anti-epileptic drug zonisamide on the development and course of alcohol dependence in rabbits. The drug co-administered with ethanol decreased alcohol-induced changes in selected brain structures. Zonisamide also decreases abstinence-induced changes in the EEG recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Being a drug with a multidirectional mechanism of action, zonisamide could modulate the activity of the hippocampus and neurotransmitter pathways involved in memory processes. Our previous pharmaco-electroencephalography study found that zonisamide decreased alcohol-and abstinence-induced changes in selected brain structures involving the hippocampus [17]. Hence, the aim of the present study was to assess the effect of zonisamide on memory processes during prolonged exposure to ethanol and also after its discontinuation.…”
Section: Introductionmentioning
confidence: 91%
“…Being a drug with a multidirectional mechanism of action, zonisamide could modulate the activity of the hippocampus and neurotransmitter pathways involved in memory processes. Our previous pharmaco-electroencephalography study found that zonisamide decreased alcohol-and abstinence-induced changes in selected brain structures involving the hippocampus [17]. Hence, the aim of the present study was to assess the effect of zonisamide on memory processes during prolonged exposure to ethanol and also after its discontinuation.…”
Section: Introductionmentioning
confidence: 91%
“…Also acts via inhibition of 'T' type calcium current. It also alters the concentration of γ-glutamyl-transferase which is a measure of alcohol consumption [97] Open-label study as per DSM-IV demonstrated that, zonisamide treatment cause significant improvement in the visual analogue scale for craving severity scores and weekly drink consumption in 22 outpatients [98] Muscles fatigue, somnolence, dizziness and ataxia [98] Pregabalin (Maximum 450 mg/day) Newer congener of gabapentin Pregabalin is selectively binds to the α2 subunit of voltagegated calcium channels and inhibits the release of excitatory neurotransmitters [99] In the open-label trial, treatment with pregbalin caused a significant progressive reduction of both craving and withdrawal symptomatology in 20 patients compared to placebo [100] Rashes, allergic reactions Baclofen (30-180 mg/day) Centrally acting muscle relaxant, reduces the acquisition of alcoholdrinking behaviour A selective GABA B receptor agonist, voltage-gated N-type calcium channel blocker and also acts as a suppressor of alcohol-stimulated dopamine release in the mesolimbic dopamine system probable mechanism in the treatment of AUD [101] In preclinical studies treatment with baclofen showed dose-dependent reduction in the self-administered alcohol in rats under operant self-administration conditions [102] Drowsiness, weakness, dizziness, tiredness, trouble sleeping, headache nausea, constipation, increased urination [102] Ondansetron (4 μg twice daily)…”
Section: Vareniclinementioning
confidence: 99%
“…A clinical study indicated that zonisamide reduced the stimulatory impacts of AA in patients [22]. Previous studies have used various dosages of zonisamide across different species (rabbits at 3-30 mg/kg [23,24], mice at 0, 25, 50 mg/kg [25], and rats at 25-50 mg/kg [25,26]), indicating its effectiveness against neurological complications. Kumar et al [27] studied a higher dose of zonisamide (100 mg/kg) in rats and demonstrated significant neuroprotective potential against seizures by mitigating oxidative stress, inflammation, and neuronal death, indicating its promise as a neuroprotective agent for epilepsy and other neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%